Favorite battlegrounds of climate action: arguing about scientific consensus, representing science-society relations - Uzelgun, M. A. (2017)
This article examines how two conflicting views regarding science-society relations—science as the arbiter of truth and as a social endeavor—perpetuate a tension in the way scientific consensus and evidence are called upon in climate change debate. In our analysis of interviews with climate change campaigners, we employ argumentation theory and social representations theory to identify and account for three discursive strategies of responding to climate contrarian arguments: direct confrontation by dichotomous arguments, de-dichotomization by addressing background assumptions, and concession to minor scientific uncertainties. We discuss these strategies emphasizing the science-society relations evident in each.